Przekształć sumy algebraiczne redukując wyrazy podobne.
1 -5a +(6a-2b +7)
2 (- 4n+ 5m) + (-6m+ 7n)
3 (-3ab + 4b-6b)-(3ab-7a +8b)
4 -(2x + 2y) - Z-(-5x - 3y + 3z)
5 [4+1-2a-(-4a+46-6)]
6 4/7a+[-(0,4-1a) - b-(2/7b-a)]
7 -3√2x² + 2x²y - 2xy + √2x² - 6xy
8 1,8xy2 +6,2x'y-5,8x²y² +0,35 yx² - 3,25 y² x
9 4/9x-2/3y-1/3x+2/15y
10 6√3xy - 3,2x² + √3xy - 7√3x - 2,8x²​


Odpowiedź :

Odpowiedź:

Szczegółowe wyjaśnienie:

[tex]1)\\-5a+(6a-2b+7) = -5a + 6a - 2b + 7= a-2b+7\\\\2)\\(-4n+5m)+(6m+7n)= -4n+5m+6m+7n=3n+11m\\\\3)\\(-3ab+4b-6b)-(3ab-7a+8b)=-3ab+4b-6b-3ab+7a-8b=-3ab-3ab+4b-6b-8b+7a=-6ab-10b+7a\\\\4)\\-(2x+2y)-z-(-5x-3y+3z)=-2x-2y-z+5x+3y-3z=3x+y-4z\\[/tex]

5)

[[tex]{4+1-2a-(-4a+46-6)[/tex]]=[tex]5-2a+4a-40=-35+2a[/tex]

6)

[tex]\frac{4}{7a} +(-(\frac{4}{10} -1a)-b-(\frac{2}{7b}-a) )=\frac{4}{7a}+(-\frac{4}{10} -1a-b-\frac{2}{7b}+a)=\frac{4}{7a}-\frac{4}{10} -1a-b-\frac{2}{7b}+a=\frac{4}{7a} -1a+a-b-\frac{2}{7b}-\frac{4}{10}=\frac{4}{7a}-b-\frac{2}{7b}-\frac{4}{10}[/tex]

7)

[tex]-3\sqrt{2x^{2} }+2x^{2} y-2xy+\sqrt{2x^{2} } -6xy=2x^{2} y-2\sqrt{2x^{2} }-8xy[/tex]

8) jest lub bo nie wiem co ten ukośnik miał znaczyć

[tex]1.8xy^{2} +6.2x\x^{2} y-5.8x^{2} y^{2}+0.35yx^{2} -3.25y^{2} x =1.8y^{2}x +6.2x\x^{2} y-5.8x^{2} y^{2}+0.35x^{2}y -3.25y^{2} x =6.55x^2y-1.45y^2x-5.8x^2y^2 \\lub\\1.8xy^{2} +6.2x y-5.8x^{2} y^{2}+0.35yx^{2} -3.25y^{2} x =1.8y^{2}x +6.2xy-5.8x^{2} y^{2}+0.35x^{2}y -3.25y^{2} x =-5.8x^2y^2-1.45y^2x+0.35x^2y+6.2xy[/tex]

9)

[tex]\frac{4}{9x}-\frac{2}{3y}-\frac{1}{3x} +\frac{2}{15y} =\frac{4}{9x} -\frac{1*3}{3x*3} -\frac{2*5}{3y*5} +\frac{2}{15y} =\frac{4-3}{9x}+ \frac{-10+2}{15y} =\frac{1}{9x} -\frac{8}{15y}[/tex]

10)

[tex]6\sqrt{3} xy-3.2x^{2} +\sqrt{3} xy-7\sqrt{3}x-2.8x^{2} =7\sqrt{3}xy-6x^{2} -7\sqrt{3} x[/tex]